Pierre Robin sequence: case report, the relevance of autopsy - Cristiano C. Oliveira; Maria Aparecida C. Domingues (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACTPierre Robin sequence is a neonatal disorder characterized by micrognathism, glossoptosis and cleft palate. We reported an autopsy case of a child whose malformations of the oropharynx were identified only at birth. The child was extremely preterm with severe neonatal depression and poor recovery, and the orofacial alterations prevented the correct treatment. There was facial disorder characterized by micrognathia associated with cleft palate and posterior displacement of the tongue, compressing the vallecula, structurally compatible with glossoptosis. This autopsy surpassed the scientific and epidemiological relevance, allowing the family genetic counseling and close monitoring of a subsequent pregnancy.